A Risk Factor which Can Induced Premature CAD in Women with Positive Family History : A Case Report - Arif Wicaksono; Mohammad Saifur Rohman; Evit Ruspiono; Cholid Tri Tjahjono (Universitas Brawijaya, 2022)
Background: Premature Coronary Artery Disease (CAD) was defined as the incidence of CAD in males younger than 45 years of age and in women younger than 55 years of age. Many factors can cause a woman under the age of 55 to develop a CAD. One of the major roles is the patient's family history associated with the occurrence of CAD which is then associated with one or more other CAD-related risk factors such as hypertension, history of Cerebrovascular Accident (CVA), obesity or dyslipidemia.Objective: This case report was made to elaborate on the importance of family history of PCAD on CAD diagnosis.Case Presentation: A 47-year-old woman who has not yet experienced menopause comes with complaints of Dyspneu on Effort (DOE). She had multiple history of CVA. She is the 2nd child of 3 siblings. Her father has died due to liver problem. Her mother had a CVA at the age of 62 with history of hypertension. Her uncle from different grandmothers, also had a history of sudden death. She was diagnosed with a coronary artery disease and percutaneous coronary intervention was performed.Conclusion: The mortality rate of women with CAD is higher than that of men, confirming that CAD in women who appear at the age of less than 55 years should receive more attention, and the task of health workers here is to strengthen history taking related to family history in women with traditional risk factors who have the possibility of developing CAD in the future.